(untitled) (Economic and Political Thought, 2016)
States as an object of study play an important cognitive role, which results from their roles in international relations. This is particularly true for global superpowers that shape the security environment worldwide. The United States and China are such entities, which as global superpowers shape international relations in the world in order to safeguard their own interests. It must be added that their goals to implement this policy may be convergent or contradictory. The present work presents the implementation of geopolitics by the United States, aimed at maintaining a dominant position in the world, including, among others, exercising control over transport routes in critical areas of the globe. In case of China, the situation is similar. It seeks to secure freedom of action on all continents of the world so as to gain economic and military advantage over its rival. Both superpowers have precisely defined geopolitical, geo-economic and geostrategic concepts, which they implement. The creation of duty free zones/free trade zones may be an example of an economic activity, and strategic concepts adopted by both the United States and China – an example of a military action.